Vegetation and climatic changes during the Middle Miocene in the Wushan Basin, northeastern Tibetan Plateau: Evidence from a high-resolution palynological record. (1st October 2017) - Hui, Zhengchuang; Li, Jijun; Song, Chunhui; Chang, Jing; Zhang, Jun; Liu, Jia; Liu, Shanpin; Peng, Tingjiang
Graphical abstract: Highlights: Based on a pollen record, we reconstructed the Mid-Miocene vegetation and climate changes in the Wushan Basin. The pollen assemblages indicate that the MMCO was also a period of climatic instability. The Mi-3b exerted a major impact on Mid-Miocene vegetation, climate and biota across central Asia. Global climate change was the first order mechanism driving Mid-Miocene vegetation and climate changes in this region. Abstract: There remains no detailed record of the Middle Miocene vegetation and climatic changes which occurred in central Asia and their possible driving mechanisms. This is because there is still a lack of high resolution records. Here, we present a sporopollen record from the Wushan Basin on the northeastern Tibetan Plateau, central Asia, spanning the period ∼16.1–13.6 Ma. The sporopollen record shows that a dense mixed forest growing in rather warm and humid climatic conditions was affected by a general drying trend during the period ∼16.1–15 Ma. It demonstrates that although the climate was generally warm and humid during the Middle Miocene Climate Optimum (MMCO), it was also a time of climatic instability. The dense forest gave way to an open forest in response to a less humid climate between ∼15 and 14.4 Ma. Dense mixed forest made a return with an increasingly humid climate during ∼14.4–13.8 Ma. This vegetation and climatic succession could be associated with global cooling, or more particularly, a higher temperature rebound set against the background of a long-term cooling trend. A more open forest appearing in response to drier and colder climatic conditions dominated the study area during the ∼13.8–13.6 Ma period. This could be compared to the rapid global cooling event Mi-3b. This significant global cooling event exerted a major impact on terrestrial vegetation, climate and biota. Our high resolution sporopollen record demonstrates that global climate changes could have been the first order driving force for the Middle Miocene vegetation and climate changes seen in the Wushan Basin in central continental Asia, with the tectonic uplift of the Tibetan Plateau probably playing a subordinate role.